Dylematy nauczania komunikacji interkulturowej na przykładzie zajęć języka obcego dla studentów ekonomii - Harbig, Anna Maria (Is It Possible to Teach Intercultural Communication? Based on Classes in a Foreign Language for Students of Economics, 2008)
The terms "intercultural communication" and "intercultural competence" appear in both foreign language teaching and in the theory and practice of economic sciences. In this research paper I have tried to explore the questions of how far the major courses of students of economics and the teaching of a foreign language are correlated to each other, how they interact and how they could influence each other. For this purpose I quote the definitions of the terms of intercultural communication and competence and present the results of empirical research among managers as to their ability to act i international contexts. In addition the framework conditions of intercultural education for students of economics are discussed using tire example of Germany and Poland. With this background I present my observations from classes in a foreign language for students of economics on negotiations.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 183-192